Islamic guidelines for content creators: A jurisprudential framework - Mustafa Mat Jubri Shamsuddin; Mohd Fuad Md Sawari; Fatimah Karim (Universiti Sains Islam Malaysia, 2025)
Ulum Islamiyyah, Volume 37 Issue 03 Page (46–63)